Alloying behaviour and microstructural changes of a Ti-10%Mo-10%Cr alloy on sintering process - Junaidi Syarif; Eko Kurniawan; Tubagus N. Rohmannudin; Mohammad Rasidi Mohammad Rasani; Zainuddin Sajuri (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aimed to investigate the effects of element diffusion on the alloying behaviour and microstructure of a Ti-10%Mo- 10%Cr alloy during sintering and furnace cooling. A theoretical calculation of the average diffusion distance for each element was performed to predict the alloying behaviour during sintering and furnace cooling. The Ti-10%Mo-10%Cr alloy was fabricated using a blended element powder metallurgy approach. Micrograph of the samples after sintering showed bright-circle structures and significantly decreased equiaxed structures. The number of plate-like structures increased with prolonged sintering time. Microstructural changes occurred because of element diffusion resulting from the prolonged sintering time. Moreover, the diffusion distance of each element also increased with prolonged sintering time. Although elements can sufficiently diffuse during both sintering and furnace cooling, the diffusion distance during sintering was considerably higher than that during furnace cooling for all elements. The diffusion distances of Cr and Mo were the highest and lowest, respectively, during sintering and furnace cooling. This study showed that alloying behaviour mostly occurred during sintering and was controlled by the diffusion of Mo atoms.